2007
DOI: 10.1529/biophysj.107.105452
|View full text |Cite
|
Sign up to set email alerts
|

Charge Separation and Energy Transfer in the Photosystem II Core Complex Studied by Femtosecond Midinfrared Spectroscopy

Abstract: The core of photosystem II (PSII) of green plants contains the reaction center (RC) proteins D1D2-cytb559 and two core antennas CP43 and CP47. We have used time-resolved visible pump/midinfrared probe spectroscopy in the region between 1600 and 1800 cm(-1) to study the energy transfer and charge separation events within PSII cores. The absorption difference spectra in the region of the keto and ester chlorophyll modes show spectral evolution with time constants of 3 ps, 27 ps, 200 ps, and 2 ns. Comparison of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 42 publications
(141 reference statements)
3
62
1
Order By: Relevance
“…A fit based on a kinetic model suggested that the slower trapping observed in CP47-RC is caused by a shift of the excited states distribution toward the CP47 antenna, and that the intrinsic rate for energy transfer from CP47 to RC does not limit the overall trapping kinetics in the CP47-RC complex. In contrast to these experimental studies recent resolved visible pump/mid-IR probe studies of the plant PSII core complexes (Pawlowicz et al 2007) and structure-based theoretical calculations (Saito et al 2006) are both in agreement with slow energy transfer from CP43/CP47 antenna to the RC.…”
Section: Modeling Of Excitation Transfer and Trapping In Isolated Reamentioning
confidence: 68%
See 1 more Smart Citation
“…A fit based on a kinetic model suggested that the slower trapping observed in CP47-RC is caused by a shift of the excited states distribution toward the CP47 antenna, and that the intrinsic rate for energy transfer from CP47 to RC does not limit the overall trapping kinetics in the CP47-RC complex. In contrast to these experimental studies recent resolved visible pump/mid-IR probe studies of the plant PSII core complexes (Pawlowicz et al 2007) and structure-based theoretical calculations (Saito et al 2006) are both in agreement with slow energy transfer from CP43/CP47 antenna to the RC.…”
Section: Modeling Of Excitation Transfer and Trapping In Isolated Reamentioning
confidence: 68%
“…Interestingly the ''effective'' rates (Groot et al 2005b;Holzwarth et al 2006b) and photosystem II core particles (c, d), ref. (Holzwarth et al 2006b;Pawlowicz et al 2007). Values of the rate constants are in 1/ns Photosynth Res (2008) 97:75-89 79 for charge separation and recombination determined by kinetic analysis (Fig.…”
Section: Modeling Of Excitation Transfer and Trapping In Isolated Reamentioning
confidence: 99%
“…This finding has triggered, however, a discussion on the nature of the primary electron donor in PSII RCs (Van Brederode et al 1999;Dekker and van Grondelle 2000). Recently, the data have been presented suggesting that the lowest excited state in the PSII RC was not necessarily localized on the ''special pair'' P680* and could be on Chl D1 * (Prokhorenko and Holzwarth 2000;Diner et al 2001;Diner and Rappaport 2002;Barter et al 2003;Germano et al 2004;Groot et al 2005;Holzwarth et al 2006;Pawlowicz et al 2007;). However, for example, the photon echo data (Prokhorenko and Holzwarth 2000) are mostly based on excitonic calculations including the site energies which are not well defined yet.…”
Section: Discussionmentioning
confidence: 99%
“…One is a self-dissipation pathway for the every chlorophyll, in which one unit of excitation leaves the network in one nanosecond [20]. The other one, for nodes in the reaction center, is charge separation, which happens in the picoseconds [21]. To solve the technical problem, we add auxiliary, dummy nodes to express the effects of charge separation and self-dissipation.…”
Section: Details Of the Network Construction And Dynamic Simulationmentioning
confidence: 99%
“…This impressive mechanism begins from the EET in PSII that is located on thylakoid membrane of chloroplast in photosynthetic cells [1]. Especially, there are many experiments focusing on relating the structure and EET properties [2,3,4]. Because the chlorophylls in these pigment-protein complexes are arranged in a peculiar pattern, many researchers have studied the overall EET of system with the orientation and distances of pigment in protein environment [5,6].…”
Section: Introductionmentioning
confidence: 99%